Characteristics and dissemination of phase I trials approved by a UK Regional Office in 2012 - Odutayo, A; Copsey, B; Dutton, S; Cook, J; Hopewell, S; Altman, D (American Medical Association, 2017)
Oversights in the design and conduct of phase I trials have resulted in morbidity and mortality1,2. Empirical evidence to improve regulatory review of phase I trials is lacking. We studied the characteristics of phase I trials, frequency of harms, and dissemination of results.